Power Relationsn in the Film Tangkal by Naza Manas - Friska Handayani; Irwan Irwan (Jurnal Hata Poda, 2025)
The film "Tangkal" by Naza Manas is a work that depicts power relations in the context of Malay culture, focusing on the figure of Pak Long Akbar as a healer who is respected in society. Through analysis using the theory of power relations by Michel Foucault, this film shows how power is not only centered in formal institutions, but is also spread in everyday social interactions. In this film, Pak Long Akbar has significant power in healing practices, where society believes in his ability to overcome spiritual problems that are considered unsolvable by conventional means. However, on the other hand, there is resistance from his son, Bullah, who tries to oppose his father's practices which are considered idolatrous and not in accordance with religious teachings. The conflict between Pak Long and Bullah reflects resistance to existing power, where Bullah struggles to change society's perspective on the healing practices carried out by his father. Bullah shows concern about the risks that Pak Long might face and tries to remind his father of the potential dangers of the practice. In this case, Bullah not only rejects his father's power, but also tries to direct society to a path that is more in accordance with religious teachings. This tension between tradition and modernity creates a complex dynamic, where Bullah tries to find his own identity in the context of different values. Overall, the film "Tangkal" depicts how power relations operate in society through the interactions between the existing characters. Through this analysis, we can see that power is not only oppressive, but also produces resistance and subjectivity. The film functions as a mirror that reflects the ongoing social and cultural dynamics, and shows how individuals can play an active role in existing power relations. Thus, "Tangkal" is not only a work of art, but also a tool for social reflection and education for its audience, inviting them to reflect on the values that exist in society and how they can contribute to positive social change.